Evaluasi Area Kebakaran Lahan dan Hutan Berbasis Hotspot Citra Modis - Adam, Sahrul S (Fakultas Teknik, Universitas Tadulako, 2020)
Land and forest fires in Malifut sub-district, North Halmahera that occurred in 2015 were the largest fires in the last 20 years, these fires have consumed most of the land and forest areas. The extent of land and forest areas is a challenge in predicting and anticipating fires. For this reason, the use of hotspot information becomes an important part of monitoring new possibilities related to fire in the following years. This study aims to identify land and forest fires by testing the distribution of hotspots resulting from the interpretation of MODIS imagery on fire hazard maps and maps of land and forest cover in Malifut sub-district. The method used is descriptive with scoring and overlays as techniques of data analysis. Data processing uses ArcGIS software version 10.6 by performing mathematical operations and shapefile hotspot data inputting. The results of this study show that there are a total of 54 hotspots in Malifut sub-district, of which 48 hotspots (88.89%) are spread in high-hazard areas, in the medium class as many as 6 hotspots (11.11%) and low class no hotspots (0%). For the results of the identification of the distribution of hotspots on the land cover map, it is found that the highest distribution of hotspots is on dry land agriculture with 34 hotspots (62.96%), shrub land with 11 hotspots (20.37%), production forests with 7 hotspots (12.96%), and forests secondary dry land and settlement each have 1 hotspot (1.85%).Â